Segurança alimentar e nutricional na assistência estudantil universitária : contribuições e limites - Martins, Cristiane Arielly Crispim (2023)
The research that resulted in this dissertation had as its object the student assistance focused on food at UFMT in the perspective of guaranteeing Food and Nutritional Security to students of undergraduate courses on campuses of Cuiabá and Várzea Grande, in the years 2019 to 2022. Through the application of a structured questionnaire, it verified how these students were fed during this period, recorded their perception of their physical and mental health status and measured food security (SA) or food insecurity (IA) through the brazilian scale of food insecurity (EBIA). At the same time, it investigated the application of the financial resources foreseen for the food assistance program in that period. Making use of the method of analysis of historicaldialectical materialism, it sought to apprehend how the theoretical categories social policy (Behring and Boschetti, 2011), student assistance (Moreira, Bavaresco and Silva, 2021) and food and nutrition security (Leão et al., 2013) are intertwined in the formation of the totality around the object. It verified that the unthinkable pandemic situation brought to light weaknesses in the student assistance (AE), subjecting its beneficiaries to various levels of food insecurity (IA), crossed by socioeconomic, gender and race elements. It also found that the budget allocated to student assistance (AE) in federal institutions of higher education (IFES) is out of step with its constitutive objectives, reflecting the contradiction generated by the clash between policies to reduce social inequalities and the capitalist economic model. Finally, it reflects the Food and Nutritional Security (SAN) not only from the perspective of the practical and immediate result of the food on the plate, but for management models that aim at both income distribution and the creation of a legacy for its users and the community. Thus, it suggests that any action taken in favor of Food and Nutritional Security (SAN) in the student assistance (AE) must be based on confronting the economic-political-social structure that generates inequality, poverty and hunger.